Hard X-ray view of the γ-ray binary LS I +61°303 - Saavedra, Enzo Agustin (2023)
In this paper, we present the results of a study of the X-ray emission of the source LS I +61°303 detected by the NuSTAR satellite. The observation was made on August 14, 2017, with an exposure of 55 ks. The lightcurve in the energy range from 3 to 79 keV is dominated by persistent emission of ∼ 0.5 c/s, for a bin of 5 s. Superposed to this emission, two microflares were detected with a maximum intensity of 1.5 c/s. Spectral analysis showed that an absorbed power law is sufficient to describe the spectrum. The power law index (E-Γ) was 2. We briefly describe a physical scenario where this emission can occur.